2021
DOI: 10.22331/q-2021-04-08-429
|View full text |Cite
|
Sign up to set email alerts
|

Towards Quantum One-Time Memories from Stateless Hardware

Abstract: A central tenet of theoretical cryptography is the study of the minimal assumptions required to implement a given cryptographic primitive. One such primitive is the one-time memory (OTM), introduced by Goldwasser, Kalai, and Rothblum [CRYPTO 2008], which is a classical functionality modeled after a non-interactive 1-out-of-2 oblivious transfer, and which is complete for one-time classical and quantum programs. It is known that secure OTMs do not exist in the standard model in both the classical and quantum set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In 2013, Broadbent et al showed that ideal classical OTMs are sufficient for non-interactive unconditionally secure quantum computation [10]. Broadbent et al also proposed an OTM construction using tamper-proof classical hardware token along with a quantum key [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Broadbent et al showed that ideal classical OTMs are sufficient for non-interactive unconditionally secure quantum computation [10]. Broadbent et al also proposed an OTM construction using tamper-proof classical hardware token along with a quantum key [11].…”
Section: Introductionmentioning
confidence: 99%